A comparative study of inhalational therapy versus supportive management in children aged 2 months to 2 years suffering from acute bronchiolitis - Ahmed, Shaik Nazeer; Poosala, Suman (International Journal of Contemporary Pediatrics, 2018)
Background: The study was conducted with the aim to compare the effectiveness of nebulized hypertonic (3%) saline and nebulized salbutamol over supportive management to assess and monitor the clinical response in the above three modalities of management, to compare the length of stay in the hospital and to identify the risk factors for severe disease. Methods: This descriptive, cross-sectional hospital-based study was conducted at RICH Pediatric Hospital, Pogathota, Nellore, Andhra Pradesh from January 2015 to October 2016. A total of 120 children were included in the study. They were randomized into three treatment groups consisting of 40 in each. Group A received only supportive management, Group B received nebulization with 4 ml of 3% hypertonic saline along with supportive management and Group C received nebulization with 2.5 ml (2.5 mg) of salbutamol along with supportive management. Nebulization were given at intervals of 4 hours, six times a day until the patient was ready for discharge. Data was entered in Microsoft excel and analysis was done using SPSS version. A p-value of <0.05 was considered to be statistically significant. Results: Out of 120 children involved in the study, majority 56 (46.66%) children were <6 months age. Male preponderance was observed in the study (M:F-1.4:1). Higher proportion of moderate to severe cases was from rural area (61 cases). More severe cases were seen in lower socioeconomic class people and who had history of second hand smoking (21.67%). Clinically better improvement was seen in children that received nebulized hypertonic saline along with supportive management with mean length of hospital stay of 2.5 days when compared to only supportive management with mean length of hospital stay of 3.25 days. The mean length of hospital stays with nebulized salbutamol along with supportive management is 3.05 days which is not clinically significant. Of the 120 children studied, 118 (98.33%) survived and were discharged, while 2 children who presented critically succumbed to death (1.67%). Conclusions: Therapy with nebulized 3% hypertonic saline reduced the length of hospital stay in children <2 years suffering from acute bronchiolitis. Due to the efficacy and cost-effectiveness of the treatment, nebulized hypertonic saline should be considered for clinical management of acute bronchiolitis in children <2 years.